Oxidation of sulfamethazine by peracetic acid activated with biochar: Reactive oxygen species contribution and toxicity change. (15th November 2022) - Zhang, Zhibo; Duan, Yanping; Dai, Chaomeng; Li, Si; Chen, Yuru; Tu, Yaojen; Leong, Kah Hon; Zhou, Lang
Abstract: Peracetic acid (PAA) as an emerging oxidative has been concerned increasingly due to its high oxidation capacity and low byproducts formation potential. This study was to investigate the oxidation of sulfamethazine (SMZ) by PAA activated with activated biochar (ABC) after thermal modification. The results demonstrated that PAA could be effectively activated by ABC to degrade SMZ in a wide pH range (3–9), which followed the pseudo-second-order kinetics ( R 2  > 0.99). Both non-radicals (singlet oxygen) and free radicals (alkoxy radicals, hydroxyl radicals) existed in the ABC/PAA system, and the degradation of SMZ was dominated by singlet oxygen. Humic acid (HA), SO4 2− and HCO3 − slightly inhibited the degradation of SMZ in the ABC/PAA process, while Cl − and Br − promoted the degradation of SMZ. The cleavage of S–N, S–C bond, and SO2 extraction reaction rearrangement was the main oxidation process of SMZ. Meanwhile, the results of the ECOSAR program showed that the acute toxicity of most by-products was significantly reduced compared to SMZ, which revealed the potential applicability of the ABC/PAA process in the treatment of antibiotics pollution and their detoxification. Graphical abstract: Image 1 Highlights: Thermally modified ABC can excellently activate PAA for SMZ degradation. The degradation of SMZ was dominated by 1 O2 . Cl − and Br − promoted the degradation of SMZ. Toxicity of SMZ was reduced after oxidation with the ABC/PAA system.